Positive effects of high salinity can buffer the negative effects of experimental warming on functional traits of the seagrass Halophila ovalis. (September 2020) - Ontoria, Y.; Webster, C.; Said, N.; Ruiz, J.M.; Pérez, M.; Romero, J.; McMahon, K.
Abstract: Coastal ecosystems, and especially estuaries, are subject to environmental fluctuations that can be amplified by anthropogenic changes. Under a future scenario of global warming, temperature and salinity are likely to be altered and the persistence of macrophyte-dominated ecosystems can be compromised, particularly native or local seagrass communities. This study examined the response of the local seagrass Halophila ovalis to the joint effect of a short-term salinity increase and a transient temperature stress, through two mesocosm experiments. Warming caused a decline in Fv /Fm, TNC content in leaves and plant growth, and increased dark respiration, revealing clear detrimental symptoms of heat stress on plant metabolism and performance. Salinity increase in isolation favoured ramet survival. However, in combination with warming, salinity had a positive effect on Gross Pmax . This suggests that increased salinities might dampen the negative effects of high temperatures, buffering, to some extent, the impact of global warming in temperate estuaries. Highlights: High temperature adversely affects H. ovalis at biochemical and physiological level. Increased salinity has no negative effects on Halophila ovalis plant performance. The simultaneous occurrence of warming and high salinity shows interactive effects. High salinities seem to buffer the impacts of transient warming.